The Integrin β1 Subunit Transmembrane Domain Regulates Phosphatidylinositol 3-Kinase-dependent Tyrosine Phosphorylation of Crk-associated Substrate - Armulik, Annika (The American Society for Cell Biology, 2004)
Our previous studies on the transmembrane domain of human integrin subunits have shown that a conserved basic amino acid in both subunits of integrin heterodimers is positioned in the plasma membrane in the absence of interacting proteins. To investigate the possible functional role of the lipid-embedded lysine in the mouse integrin β1 subunit, this amino acid was replaced with leucine, and the mutated β1 subunit (β1A(K756L)) was stably expressed in β1-deficient GD25 cells. The extracellular domain of β1A(K756L) integrins possesses a competent conformation for ligand binding as determined by the ability to mediate cell adhesion, and by the presence of the monoclonal antibody 9EG7 epitope. However, the spreading of GD25-β1A(K756L) cells on fibronectin and laminin-1 was impaired, and the rate of migration of GD25-β1A(K756L) cells on fibronectin was reduced compared with GD25-β1A cells. Phosphorylation of tyrosines in focal adhesion kinase (FAK) and the Y416 in c-Src in response to β1A(K756L)-mediated adhesion was similar to that induced by wild-type β1. The tyrosine phosphorylation level of paxillin, a downstream target of FAK/Src, was unaffected by the β1 mutation, whereas tyrosine phosphorylation of CAS was strongly reduced. The results demonstrate that CAS is a target for phosphorylation both by FAK-dependent and -independent pathways after integrin ligation. The latter pathway was inhibited by wortmannin and LY294002, implicating that it required an active phosphatidylinositol 3-kinase. Furthermore, the K756L mutation in the β1 subunit was found to interfere with β1-induced activation of Akt. The results from this study identify phosphatidylinositol 3-kinase as an early component of a FAK-independent integrin signaling pathway triggered by the membrane proximal part of the β1 subunit.